Design, development and pilot of a realistic virtual reality application to analyse quick directional change in sport: Avatar cutting scenario with alterable parameters. - Hannah K M Tang; Mark J Lake; Richard J Foster; Frederic A Bezombes (PLoS ONE)
Injuries during quick directional change (cutting) are common, particularly to the anterior cruciate ligament of the knee. Cutting is subsequently a focus in research and clinical practices. However, it is usually assessed in situations with low ecological validity. As a solution, virtual reality (VR) has been used to replicate sporting scenarios. The current paper details the design, development, and piloting of a VR application based on an unanticipated-cutting scenario using an avatar-opponent blocking manoeuvre. The VR environment is highly realistic, avatar approach is instigated by the movement of the headset user, and simple input alters the avatar's movements and spatiotemporal demands of the cutting task. Piloting occurred in two stages: the first involved three participants and focused on initial system testing and parameter optimisation, the second focused on a pilot case study with a female participant of typical population. The case study evaluated the effects of using different visual cutting cues on frontal plane knee kinematics and kinetics linked to injury risk. Twenty-five successful, unanticipated, 90⁰ cutting manoeuvres to the left were analysed in three conditions: 1) physical world with arrows, 2) VR environment emulation with VR arrows, 3) VR environment emulation with VR avatar opponent. Mean knee angle during the arrow conditions, both physical and VR, presented abduction angles (-8.82° ± 1.44; -2.66° ± 0.90), yet cutting around the avatar opponent presented knee adduction angles (9.78° ± 0.44). During the 50 ms prior to heel strike, pelvis velocity was lowest and cutting foot velocity highest in the avatar condition compared to arrow conditions. This indicated the VR environment acts as a suitable control and that cutting strategy was adapted approaching the avatar, displaying more caution on approach. The avatar-based application has the potential to improve the ecological validity of cutting assessment and make a VR application more accessible to researchers and clinicians, with further development.